Портали в оздобленні визначного храмового ансамблю Львова - Чень, Леся; Chen, Lesya (Видавництво Львівської політехніки, 2022)
Показано роль порталів в оздобленні храмового ансамблю Успення Богородиці у Львові. На прикладі порталів собору Успення Богородиці, каплиці Трьох Святителів та вежі-дзвіниці розглянуто особливості використання декоративної різьби в камені у пластичному вирішенні фасадів сакральних споруд в період ренесансу у Львові. Проаналізовано композиційні й стилістичні особливості ренесансних порталів споруд храмового ансамблю. Із метою фізичного збереження унікальних порталів, визначних творів мистецтва та архітектури, окреслено комплексні заходи їх реставрації.

In artistic and stylistic terms, the architecture of Lviv's sacred buildings during the 16th-18th centuries was marked by a variety of appearances. The builders paid great attention to the plastic expressiveness of the building. The facades of sacred buildings were richly decorated, had a clear system of horizontal divisions of cornices and belts, carved in stone with ornamental carvings window frames, and portals of entrances. The role of portals in the decoration of the church ensemble of the Assumption of the Virgin in Lviv is shown. The peculiarities of the use of decorative stone carvings in the plastic design of the facades of sacred buildings during the Renaissance in Lviv are considered on the example of the portals of the Assumption Cathedral, the Chapel of the Three Saints, and the bell tower. The compositional and stylistic features of the Renaissance portals of the temple ensemble are analyzed. In order to physically preserve unique portals, outstanding works of art, and architecture, comprehensive measuresfortheirrestoration are outlined.
Portals in decoration of buildings of the assembly of the assumption of the virgin in Lviv
Keywords: ансамбль собору Успення Богородиці; каплиця Трьох Святителів; пластичне оздоблення; портали; композиція; пропорції; декор; реставраційні заходи; ensemble of the Cathedral of the Assumption of the Virgin; chapel of the Three Saints; plastic decoration; portals; composition; proportions; decor; restoration measures; 726; 27-523.4(477.83)